AN INVESTIGATION INTO THE APPLICABILITY OF NATURAL LOAD VARIATION SCHEME TO THE MEASUREMENT OF ENERGY YIELD OF PHOTOVOLTIC MODULE (Nigerian Journal of Technology, 2017)
Currently, photvoltaic (PV) modules are characterized based on open circuit voltage, short circuit current as well as voltage and current at maximum power point under strictly specified laboratory conditions. Among manufacturers, regulators and experts, this approach appears reasonably adequate. Nevertheless, among end users and and low level technicians, it may be misleading. This is on account of the critical difference between the laboratory and in situ conditions. This often results to improper design which in turn is capable of accelerating a premature system failure. The present work explores the potentials of natural load variation scheme as a low cost option that is capable of estimating the actual yield of PV modules. Essentially, the scheme consists of a firmware controlling the switching of a number of resistors(loads) connected in parallel. By looping through the resistors in parallel, the firmware matches load impedance to the impedance of the module thus the module operates at its maximum power point. The research results indicate a similar response pattern for constant and variable loads. Nevertheless, the quantitative value of recorded voltage, current, power and energy tended to increase as the number of available resistors incresed. Though clear convergence was not achieved, natural load variation scheme more realistically captures the yield potentials of polycrystalline PV modules under low irradiance conditions. http://dx.doi.org/10.4314/njt.v36i3.28